(untitled) (Indian Journal of Nematology, 2024)
Two new taxa of nematodes, Gymnotylenchus indicus n. sp. and Sirasnema indicum n. gen., n. sp., collected from the bark of Albizia lebbeck infested with bark boring insects have been described. Gymnotylenchus indicus n. sp.: Female: L= 0.33-0.49 mm, a= 14.5-26.9, b= 6.5-8.1, c= 8.4-11.3, V= 83.9-86.7, c’= 2.6-5.0, stylet = 7-9 μm. Body obese, almost straight. Hemizonid 3-7 annuli anterior to excretory pore. Spermatheca indistinct. Post vulval uterine sac absent. Tail short, conoid, tapering from both sides to a pointed terminus. Male: L= 0.33-0.41 mm, a= 16.4-26.4, b= 5.9-6.9, c= 8.8-13.1, c’= 2.3-3.8, spicules= 12-14 μm. Spermatozoa of only one type, minute, nucleated, as seen in infective females. Spicules small and angular. Tail conoid, dorsal side almost straight, ventral side curved. Infective female: L= 0.38-0.49 mm, a=21.6-27.6, b= 4.4-5.8, c= 10.4-14.5, V= 85.5-88.6, c’= 2.9-3.7, stylet = 15-18 μm. Conus of stylet less than 1/3 of stylet length, shaft with basal swellings. Tail elongated-conoid, regularly tapering from both sides to a narrowly rounded terminus. Sirasnema indicum n. gen. n. sp.: Female: 0.52-0.62 mm, a= 24.0-28.9, b= 4.2-5.4, c= 8.1-10.6, V= 82.2-85.3, c’= 3.7-5.1, stylet = 8-10 μm, tail = 51-71 μm. Lateral lines four, hemizonid just anterior to excretory pore, basal pharyngeal bulb elongated, with a small stem-like extension, spermatheca rounded-oval with large disc-shaped sperms, post vulval uterine sac absent. Tail elongated conoid with narrowly rounded to pointed terminus. Male: L= 0.48-0.54 mm, a= 22.0-28.8, b= 4.1-5.6, c= 19.3- 27.0, c’= 1.7-2.1, spicules= 21-23 μm. Spermatozoa dimorphic, as seen in fungivorous or infective females. Tail enveloped by a high caudal alae. Infective female: Produced in old culture, L= 0.59 mm, a=28, b= 3.1, c= 11.2, V= 84.1, c’= 4.7, stylet = 14 μm. Neck region distinctly ventrally curved. Stylet with sloping, trilobed knobs. Genital tract filled with small, rounded and nucleated sperms. Post vulval uterine sac absent. Stictylus mucronatus Thorne & Malek, 1968 collected from rhizosphere of Pinus roxburghii is a new record from India.